Sub-Nucleolar Trafficking of Hendra Virus Matrix Protein Is Regulated by Ubiquitination - Tianyue Zhao; Florian A. Gomez; Cassandra T. David; Christina L. Rootes; Cameron R. Stewart; Gregory W. Moseley; Stephen M. Rawlinson (Viruses)
Hendra virus (HeV) is a highly pathogenic member of the Henipavirus genus (family Paramyxoviridae, order Mononegavirales), for which all basic replication processes are located in the cytoplasm. The HeV matrix (M) protein plays essential roles in viral assembly and budding at the plasma membrane, but also undergoes dynamic nuclear and nucleolar trafficking, accumulating in nucleoli early in infection, before relocalising to the plasma membrane. We previously showed that M targets sub-nucleolar compartments—the fibrillar centre (FC) and dense fibrillar component (DFC)—to modulate rRNA biogenesis by mimicking a process occurring during a nucleolar DNA-damage response (DDR). Here, we show that M protein sub-nucleolar localisation is regulated by ubiquitination, which controls its redistribution between the FC-DFC and granular component (GC). The mutagenesis of a conserved lysine (K258) reported to undergo ubiquitination, combined with the pharmacological modulation of ubiquitination, indicated that a positive charge at K258 is required for M localisation to the FC-DFC, while ubiquitination regulates subsequent egress from the FC-DFC to the GC. M proteins from multiple Henipaviruses exhibited similar ubiquitin-dependent sub-nucleolar trafficking, indicating a conserved mechanism. These findings reveal a novel mechanism regulating viral protein transport between phase-separated sub-nucleolar compartments and highlight ubiquitination as a key modulator of intra-nucleolar trafficking.